THE PLANNING AND ORGANIZATION OF ECT TREATMENTS IN FINLAND – RESULTS FROM A NATIONAL SURVEY - SAANA KARTTUNEN, LAURI VIRTANEN, ANU HOLM, NIKO SEPPÄLÄ, PETRI SUMIA, ERIKA JÄÄSKELÄINEN, KAIJA JÄRVENTAUSTA (Psychiatria Fennica)
ABSTRACT Objectives: The demand for acute ECT, as well as the number of maintenance ECT patients has increased in Finland. Due to the increased demand, waiting times have grown and scheduling of ECT treatments has become more complicated. The purpose of this study was to analyse the situation of ECT treatment in Finland in different neuromodulation units regarding waiting times, organizing the treatment and categorizing the urgency of the treatment. The survey was part of the first author’s development assignment for a leadership training course for psychiatrists organized by the University of Lapland and the Finnish psychiatric association. The goal of this survey was both to gather information about the current situation in different neuromodulation units and to use the information in developing the practices in the Neuromodulation unit in Oulu University Hospital. Materials and methods: A structured questionnaire in the form of a Webropol survey was used for collecting the data from different Neuromodulation units in Finland. The questionnaire included 35 questions. It was sent to the person leading the clinical work in the unit. We received a total of 22 answers, representing to our knowledge all the units currently giving ECT in Finland, except for the Åland Islands and Vanha Vaasa Hospital, which is a state forensic psychiatry unit. Results: There are large differences in both the evaluation of the need for ECT and how the treatments are organized. ECT waiting list was in use in 15/22 (68%) of the units, and patients were classified based on the urgency of the treatment in 9/21 (43%) of the units. The waiting list caused additional work. The three most important criteria used in evaluating the urgency were suicidality, psychotic symptoms in depression and catatonia as well as inpatient status. In most units, urgency was evaluated by the psychiatrist in the ECT unit. The waiting time for different patient groups varied from a few days to over a year. In 91% of the units, catatonia patients were able to start ECT within a week, whereas for non-acute outpatients with treatment-resistant depression, the waiting time in 57% of the units was 1-3 months, and in one unit over one year. The length of the acute ECT varied from 3 to 16 treatments, with a somewhat different number of treatments for schizophrenia and depression. ECT maintenance treatments were given in all 22 units, with varying protocols. In some units (41%) the length or the availability of the maintenance treatment was limited due to the resources. Conclusions: Although the criteria for urgency are largely consistent, there are more patients fulfilling ECT indications than there are resources to treat. In addition, treatments are organized in different ways and the capacity of the ECT units varies leading to different waiting times. In all units, the most acute patients get treatment fast but the variation in non-acute patients is great. As there are no national guidelines regarding practical organization of ECT treatment, collaborative efforts to identify and adopt good practices are needed. A larger survey about the treatment numbers and the technical treatment methods for different neuromodulation treatments is currently underway.